Collecting Pokémon or receiving rewards? How people functionalise badges in gamified online learning environments in the wild. Issue 127 (July 2019) - van Roy, Rob; Deterding, Sebastian; Zaman, Bieke
Highlights: There are at least nine different ways of functionalising badges. The uncovered functionalisations only partly align with prior theorisations. Badge design details foster but do not determine different functionalisations. Users' functionalisations impact their experience, motivation and behaviour. The functional significance-framework is useful for understanding gamification. Abstract: Do game design elements like badges have one, fixed motivational effect or can they have several different? Self-Determination Theory suggests that people situationally appraise the functional significance or psychological meaning of a given stimulus, which can result in different motivational states, but there is little empirical work observing actual functionalisations of game design elements. We therefore conducted a qualitative in-the-wild diary and interview study with 81 university students who reported on their experiences with badges on two popular gamified online learning platforms, Khan Academy and Codecademy . Participants functionalised badges in nine distinct ways that only partially align with prior theory. Functionalisations shaped experience and motivation and prompted function-aligned behaviour. Badge design details fostered but did not determine different functionalisations, while no user or context characteristics were identified that reliably linked to particular functionalisations. We conclude that future research may need to conceptualise game design elements in a more differentiated way to capture what aspects support different motivational functions.